Sectoral Wage Gaps and Gender in Rural India - Joshua D. Merfeld (Institute of Labor Economics (IZA), 2021)
Using detailed monthly panel data from rural India, this paper analyzes sectoral wage gaps for men and women. I document three important findings. First, there is clear evidence of sorting into sectors, with very large differences in worker human capital across the farm and non-farm sectors and much higher wages in the latter. Second, while these wage gaps are substantial in the cross-section, the wage gap within individuals is decidedly smaller, consistent with worker sorting. Third, the wage gap for women is much larger than it is for men, with the latter exhibiting almost no within-individual gap in wages across sectors. Women work fewer hours and are less likely to work outside of their own village in the non-farm sector, yet the wage gap is driven by higher-caste and married women. I find no evidence of non-pecuniary benefits of agricultural employment relative to non-farm employment being responsible for this gap. These results are consistent with a lack of local non-farm employment opportunities interacting with barriers to labor mobility for women but not men.
Keywords: J31; J43; Q12; 330; agriculture; gender; labor; non-farm; wages